2022
DOI: 10.2224/sbp.10853
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and depression in middle-aged and senior citizens in China

Abstract: We examined the effects of social activities on depression in middleaged and senior men and women in China. We classified social activities into informal and formal categories; the former require more intimate and intensive participation, while the latter require less. Participants were 8,610 respondents aged 45 years and above, whose data were extracted from the 8-year Chinese Health and Retirement Longitudinal Study (2011–2018) and analyzed using a fixed-effects regression model. The results provide evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, further studies are needed to verify this relationship. Consistent with previous fndings [7,[54][55][56], depressive symptoms are negatively related to social participation. Tis indicates that the degree of social participation of late-life migrants is related to their psychological functioning.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, further studies are needed to verify this relationship. Consistent with previous fndings [7,[54][55][56], depressive symptoms are negatively related to social participation. Tis indicates that the degree of social participation of late-life migrants is related to their psychological functioning.…”
Section: Discussionsupporting
confidence: 89%
“…A longitudinal study found that older adults with more depressive symptoms engaged in less social participation [53]. Tus, depressive symptom is negatively associated with social participation among older Chinese adults [7,[54][55][56]. Although depressive symptom has a reciprocal relationship with social participation, longitudinal studies have suggested that the efect of depressive symptom on social participation in older adults is stronger than the opposite efect [57,58].…”
Section: Te Mediating Efect Of Depressive Symptommentioning
confidence: 99%